2010
DOI: 10.4172/1948-5948.1000025
|View full text |Cite
|
Sign up to set email alerts
|

L(+) Lactic Acid Production by New Lactobacillus Rhamnosus B 103

Abstract: L(+) Lactic acid fermentation was studied by Lactobacillus rhamnosus sp. under the effects of pH control and a lowcost nutritional medium (sugarcane juice and corn steep liquor-CSL). Central composite design (CCD) was employed to determine maximum lactic acid production at optimum values for process variables and a satisfactory fi t model was realized. Statistical analysis of the results showed that the linear and quadratic terms of two variables (sugarcane juice and pH) had signifi cant effects. The interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
2
13
0
1
Order By: Relevance
“…These results are comparable to other studies (Mussatto et al, 2008, de Lima et al, 2010 which have found that pH control generates significant increases in lactic acid production, the consumption of the substrate and productivity. In addition, because of its role as a constituent of many enzymes, but especially lactate dehydrogenase, manganese is an essential growth factor for some lactic acid bacteria such as L. casei, (de Angelis & Gobbetti, 1999, FitzPatrick et al, 2010.…”
Section: Discussionsupporting
confidence: 82%
“…These results are comparable to other studies (Mussatto et al, 2008, de Lima et al, 2010 which have found that pH control generates significant increases in lactic acid production, the consumption of the substrate and productivity. In addition, because of its role as a constituent of many enzymes, but especially lactate dehydrogenase, manganese is an essential growth factor for some lactic acid bacteria such as L. casei, (de Angelis & Gobbetti, 1999, FitzPatrick et al, 2010.…”
Section: Discussionsupporting
confidence: 82%
“…As the synthesis of lactic acid by fermentation is associated with cell growth, there is no product formation if the medium does not have an adequate concentration of nitrogen [24]. However, high concentrations of nitrogen can lead to cell death [15].…”
Section: Response Surface Methodsmentioning
confidence: 99%
“…According to Tejayadi and Cheryan [9], the cost of raw materials represents 68% of the total cost of lactic acid production. A number of industrial bioproducts or wastes have been evaluated as substrates for lactic acid production with the aim of decreasing the cost of the process, such as sugarcane [10], molasses [11], cassava wastewater [12], and whey [13] as carbon sources and corn steep liquor (CSL) [14] and yeast autolysate [15] as nitrogen sources. However, there are a few studies on D(−)-lactic acid fermentation using these substrates in comparison with L(+)-lactic acid.…”
Section: Introductionmentioning
confidence: 99%
“…They have a long history of application in fermented foods because of their beneficial influence on nutritional, organoleptic, and shelf-life characteristics [3]. Lactic acid bacteria cause rapid acidification of the raw material through the production of organic acids, mainly lactic acid [4]. In addition, their production of acetic acid, ethanol [5], aroma compounds, bacteriocins, exopolysaccharides, and several enzymes is of importance ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%